Spectrophotometric Determination of As(III) by Colour Reduction Method - DHOMANE, A.S.; VENKATACHALAM, A. (Asian Journal of Chemistry, 2010)
Spectrophotometric method for trace determination of As(III) has been developed on the basis of reduction of absorbance of KMnO4 solution by As(III). Up to 6.0 μg/mL of As(III) can be determined with a standard deviation of 0.082 μg/mL.